2017
DOI: 10.31186/jspi.id.12.1.94-101
|View full text |Cite
|
Sign up to set email alerts
|

Tingkah Laku Reproduksi Merak Hijau (Pavo Muticus) pada Umur yang Berbeda di UD. Tawang Arum Kecamatan Gemarang, Kabupaten Madiun

Abstract: The aim of the study was determine the reproductive behavior of green peafowl with different ages. The research was conducted in October -December 2015 at UD. Tawang Arum, Tawangrejo Village, District Gemarang, Madiun. The parameter of the study were duration, frequency and sequence of the reproductive behavior of green peafowl. The result showed that reproductive behavior of 10 years male peafowl showed more reproductive behavior than other, as did the green peafowl females at aged 10 years old doing more rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
0
4
0
4
Order By: Relevance
“…This research was conducted using a focal animal sampling method. The researcher recorded all activities seen in their daily activities, and the time sampling method was used to divide the time for behavioral observation (Nareswari et al 2017). Observation of the time sampling method is to record the frequency and duration of daily behavior at periods of three hours for a total of 6 hours of observation daily starting at 06:00-09:00 am and 03:00-06.00 pm.…”
Section: Breeding Behaviors Data Collection Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This research was conducted using a focal animal sampling method. The researcher recorded all activities seen in their daily activities, and the time sampling method was used to divide the time for behavioral observation (Nareswari et al 2017). Observation of the time sampling method is to record the frequency and duration of daily behavior at periods of three hours for a total of 6 hours of observation daily starting at 06:00-09:00 am and 03:00-06.00 pm.…”
Section: Breeding Behaviors Data Collection Methodsmentioning
confidence: 99%
“…Usually, it will be followed by a mating activity. Study results on green peahen reproductive behaviors by Nareswari et al (2017) showed that reproductive hormone concentration in every age level of female birds would affect their sexual behavior pattern. The duration, frequency, and sequence of younger female green peacock birds' sexual behavior will differ from that of an older green peacock.…”
Section: Introductionmentioning
confidence: 99%
“…Sampel ayam diambil secara langsung setelah melakukan survei ayam Burgo di kandang peternak Kelurahan Pagar Dewa, Kecamatan Selebar, Kota Bengkulu. Selanjutnya, karakteristik suara kokok ayam ditetapkan dengan metode time sampling (Nareswari et al, 2017).…”
Section: Tahapan Penelitianunclassified
“…Merak betina memiliki bulu berwarna hijau kecoklatan tanpa bulu penutup ekor dan bertubuh lebih kecil daripada merak jantan. Merak jantan akan mengangkat bulu penutup ekornya yang sangat indah membentuk seperti kipas dan mengitari pasangannya serta menggoyangkan bulu penutup ekornya untuk menarik perhatian lawan jenisnya kemudian menopang diatas punggung merak betina untuk berbiak [3]. Burung merak Hijau-Jawa (Pavo muticus-muticus) merupakan subspesies dari merak hijau (Pavo muticus) yang tersebar di pulau Jawa.…”
Section: Pendahuluanunclassified
“…Merak hijau-jawa makan dengan cara mematuk makanan dengan paruhnya langsung dari wadah makanannya di dalam kandang yang sudah disediakan dan biasanya akan mengorek-ngorek makanannya lalu menumpahkannya ke tanah kemudian mematuknya kembali. Menurut [3] merak hijau memiliki cara makan yaitu mematuk dengan menggunakan paruhnya kemudian pemilihan makanan di atas permukaan tanah dengan cara mengais permukaan tanah dengan menggunakan paruh dan kakinya. Perilaku makan merak hijau-jawa dimulai dengan mengambil makanan dengan paruhnya kemudian menelannya.…”
Section: Perilaku Makanunclassified